PENGALAMAN IBU BEKERJA DALAM STRATEGI IBU MENGAJAR DAN MENDAMPINGI ANAK DARING - Ikke Ulandari; Rina Puspita Sari; H. AYG Wibisono3 (Nusantara Hasana Journal, 2022)
Background: The pandemic has changed human life, especially for working mothers who have the roles of workers and mothers, but during the pandemic, working mothers must become companion teachers for their children who do online learning. Research Objective: The exploration of the experience of working mothers in the strategy of mothers teaching and assisting children online . Research Method: Qualitative study with a phenomenological approach. There were six participants who were determined by purposive sampling method. Data were collected through in-depth interviews. Data Analysis: Collaizzi’s method. Results: Produce a strategy theme of mothers teaching and assisting children online with the sub-themes obtained are managing the time mothers work, creating communication patterens, learning methods, and delegating mentoring children online and the categories obtained are setting time discipline, time for mentoring, conducting open discussions, learning together, and part of the online assistance is handed over to the family. Conclusion: Vulnerable working mothers age 37-51 years who have school-age children aged 7-12 years. Suggestion: The results of this study were recommended, teachers, parents, nursing profession, next research.